2008
DOI: 10.1142/s0129167x08004698
|View full text |Cite
|
Sign up to set email alerts
|

Positive Mass Theorems for Asymptotically Ads Spacetimes With Arbitrary Cosmological Constant

Abstract: We formulate and prove the Lorentzian version of the positive mass theorems with arbitrary negative cosmological constant for asymptotically AdS spacetimes. This work is the continuation of the second author's recent work on the positive mass theorem on asymptotically hyperbolic 3-manifolds.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 23 publications
(61 reference statements)
0
25
0
Order By: Relevance
“…4λ 2 e j · e i · φ α + 1 4λ 2 e i · e j · φ α (14) follows from the similar argument of the second theorem in [14]. The result that M is hyperbolic and maximal becomes a consequence that there is a basis {φ α } parallel to the imaginary Killing connection.…”
Section: Proof Of the Main Theoremsmentioning
confidence: 81%
See 1 more Smart Citation
“…4λ 2 e j · e i · φ α + 1 4λ 2 e i · e j · φ α (14) follows from the similar argument of the second theorem in [14]. The result that M is hyperbolic and maximal becomes a consequence that there is a basis {φ α } parallel to the imaginary Killing connection.…”
Section: Proof Of the Main Theoremsmentioning
confidence: 81%
“…Thanks to the Lax-Milgram theorem [18] , by similar argument in [11,13,14,17,19,20], there exists a unique spinor Φ 1 in H 1 (S) such that…”
Section: Proof Of the Main Theoremsmentioning
confidence: 90%
“…Initial investigations were carried out in [1,3,27,30], the time symmetric case (k = 0) was treated in [2,18,19,49,53], and the most general versions were given in [20,38,50,52]. See also [15] for a discussion concerning the rigidity statement.…”
Section: The Positive Mass Theoremmentioning
confidence: 99%
“…In this section, we use hyperbolic coordinates and the positive mass theorem for asymptotically hyperbolic manifolds proved in [31,28] to derive a positive mass theorem for asymptotically half de Sitter spacetime. Let…”
Section: Hyperbolic Coordinates and Positive Mass Theoremmentioning
confidence: 99%
“…Anti-de Sitter spacetimes are characterized by Killing spinors with imaginary Killing constants, which have certain nice properties. Witten's method was extended successfully to asymptotically Antide Sitter spacetimes and the positive mass theorem was proved completely and rigorously in this case [25,10,31,17,28]. As recent cosmological observations indicated that our universe possibly has a positive cosmological constant, the positive mass theorem for asymptotically de Sitter spacetimes gains much more importance.…”
Section: Introductionmentioning
confidence: 99%